Quality Improvement Interventions for Early HIV Infant Diagnosis in Northeastern Uganda - Izudi, Jonathan (Biomed Res Int, 2016)
Introduction. Early infant diagnosis (EID) of human immunodeficiency virus (HIV) ensures prompt treatment and infant survival. In Kaabong Hospital, 20% of HIV exposed infants (HEIs) had access to HIV diagnosis by eight weeks. We aimed to improve EID of HIV by deoxyribonucleic acid-polymerase chain reaction (DNA-PCR) testing by eight weeks from 20 to 100% between June 2014 and November 2015. Method. In this quality improvement (QI) project, EID data was reviewed, gaps prioritized using theme matrix selection, root causes analyzed using fishbone tool, and improvement changes were selected using counter measures matrix but implemented using Plan-Do-Study-Act cycle. Root causes of low first DNA-PCR testing included maternal EID ignorance, absent lost mother-baby pairs (LMBP) tracking system, and no EID performance reviews. Health education, Continuous Medical Education (CMEs), and integration of laboratory and EID services were initial improvement changes used. Results. DNA-PCR testing increased from 20 to 100% between June 2014 and July 2015 and was sustained at 100% until February 2016. Two declines, 67% in September 2014 and 75% in June 2015, due to LMBP were addressed using expert clients and peer mothers, respectively. Conclusion. Formation of WIT, laboratory service integration at MBCP, and task shifting along EID cascade improved EID outcomes at 6 weeks.